A multicentre, multinational, randomized, placebo‐controlled, double‐blind, phase 3 trial to evaluate the efficacy and safety of gemigliptin (LC15‐0444) in patients with type 2 diabetes. Issue 5 (17th December 2012) - Yang, S. J.; Min, K. W.; Gupta, S. K.; Park, J. Y.; Shivane, V. K.; Pitale, S. U.; Agarwal, P. K.; Sosale, A.; Gandhi, P.; Dharmalingam, M.; Mohan, V.; Mahesh, U.; et al.
<x xml:space="preserve">Abstract</x> Aim This study was designed to assess the efficacy and safety of the dipeptidyl peptidase IV inhibitor gemigliptin (LC15‐0444) 50 mg versus placebo in patients with type 2 diabetes. Methods We conducted a 24‐week, randomized, double‐blind, placebo‐controlled phase III trial in 182 patients (74 from Korea and 108 from India) with type 2 diabetes. After an initial 2 weeks of a diet and exercise programme followed by 2 weeks of a single‐blind placebo run‐in period, eligible patients were randomized to gemigliptin 50 mg or placebo, receiving the assigned treatment for 24 weeks. HbA1c and fasting plasma glucose (FPG) were measured periodically, and oral glucose tolerance test was performed at baseline and weeks 12 and 24. Results At week 24, gemigliptin treatment led to significant reductions in HbA1c measurements compared to placebo (adjust mean after subtracting the placebo effect size: −0.71%, 95% confidence interval: −1.04 to −0.37%). A significantly greater proportion of patients achieved an HbA1c <7% with gemigliptin than with placebo. The placebo‐subtracted FPG change from baseline at week 24 was −19.80 mg/dl. The overall incidence rates for adverse events were similar in the gemigliptin and placebo groups. Conclusions This study showed the efficacy and safety of gemigliptin 50 mg administered once daily as a monotherapy for type 2 diabetes patients.